The Impact of Promoting Nickel Mining Services in Indonesia Using Big Media to Boost Customer Interest in Purchasing (A Case Study At PT. Putra Perkasa Abadi) - Angga Tri Saputra; Bobby W. Saputra (International Journal of Economics (IJEC), 2023)
As the nickel commodity market soars, companies that have Mining Business Permits (IUP) and Special Mining Business Permits (IUPK) in Indonesia are increasing their targets from year to year. And with this increasing target, companies holding IUPs and IUPKs increasingly need cooperation with companies holding Mining Services Business Permits (IUJP) to increase the efficiency and production volume of the mining process which includes mining construction, mining, transportation of mining products as well as reclamation and post-mining. This research used a quantitative research. The quantitative method is referred to as a scientific method because it meets scientific principles, namely, empirical, objective, measurable, rational and systematic. The results of this research indicate that the Big Media Promotion variable (X) has a positive and significant influence on Purchase Interest (Y) at PT. Putra Perkasa Abadi. Management of PT. Putra Perkasa Abadi is advised to continue to increase major media promotions, especially on social media and sponsorship at seminars so that buying interest in IUP owners throughout Indonesia continues to increase.